PENGEMBANGAN PEMBELAJARAN BIOLOGI SEL BERBASIS CONCEPT ATTAINMENT GUNA MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN PENGUASAAN KONSEP MAHASISWA - Martomidjojo, Russamsi (2012)
A study using research and development method was carried out to develop of cell biology learning based on concept attainment to improve critical thinking skills and concept mastery of students. The learning developed was implemented second semester of biology education students at one of University in West Java using quasi experiment. Data were obtained from critical thinking skills test, concept mastery test, interview, and questionnaire about comments of biology lecturers and students toward the program. The result shows that learning of cell biology based on concepts attainment could improve critical thinking skills and concept mastery higher than those of control group which learnt cell biology regularly, and the learning has been responded positively from both the students and lecturers.